2002
DOI: 10.1046/j.1537-2995.2002.00235.x
|View full text |Cite
|
Sign up to set email alerts
|

Severe autoimmune hemolytic anemia caused by a warm IgA autoantibody directed against the third loop of band 3 (RBC anion‐exchange protein 1)

Abstract: This is the first report of an IgA autoantibody directed against the band 3 (AE1) protein and, more specifically, against the third loop. Moreover, this case underlines the importance of including IgA research in the initial diagnostic evaluation when a hemolytic anemia is suspected to be autoimmune and when IgG and complement are not detected on the patient's RBCs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
22
0
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 30 publications
4
22
0
2
Order By: Relevance
“…(supplemental Table 1). Consistent with previous findings, 19,20 these results suggested that the target antigen may be located on the third external loop of Band 3, on decay-accelerating factor (DAF; CD55), or on glycophorin B (GPB; CD235). Positive agglutination reactions against rare RBCs, including Inab (DAF-deficient), M k /M k (GPB-deficient), and Rh null samples, ruled out specificity for DAF, GPB, and RhAG.…”
Section: Characterization Of the E-iga Autoantibodiessupporting
confidence: 91%
See 1 more Smart Citation
“…(supplemental Table 1). Consistent with previous findings, 19,20 these results suggested that the target antigen may be located on the third external loop of Band 3, on decay-accelerating factor (DAF; CD55), or on glycophorin B (GPB; CD235). Positive agglutination reactions against rare RBCs, including Inab (DAF-deficient), M k /M k (GPB-deficient), and Rh null samples, ruled out specificity for DAF, GPB, and RhAG.…”
Section: Characterization Of the E-iga Autoantibodiessupporting
confidence: 91%
“…Only one other case of wAIHA with IgA directed against Band 3 in a 3-year-old child has been reported. 19 However, other cases associated with IgG or IgM autoantibodies with Band 3 specificity have been described. 20,23,24 The clinical relevance of Band 3 as a target in AIHA may be related to the broad role played by this anion exchanger in RBC physiopathology and to its abundance, as it accounts for more than 30% of the proteins present on the RBC membrane.…”
Section: Discussionmentioning
confidence: 99%
“…One was IgA optimally active at 37 o C [164] ; the other cold reactive IgM plus IgG [165] . One was IgA optimally active at 37 o C [164] ; the other cold reactive IgM plus IgG [165] .…”
Section: Other Diego Antigens Di5 To Di22mentioning
confidence: 94%
“…Quatre présentaient une hémolyse sévère avec un taux d'hémoglobine inférieur à 60 g/L et deux une hémolyse intravasculaire. D'autres cas graves d'AHAI dues à ces auto-Acs ont été décrits [1,8] dont un avec hémolyse intravasculaire [2]. Par ailleurs, il est plus fréquent de rencontrer des auto-Acs IgA chauds que froids [11].…”
Section: Introductionunclassified